Deep-water Photinae (Gastropoda: Nassariidae) from eastern Africa, with descriptions of five new species - Fraussen, Koen; Galindo, Lee Ann; Rosado, José (European Journal of Taxonomy, 2020)
Deep-water species from the western Indian Ocean off the East African coast and Madagascar, belonging to the subfamily Photinae, are discussed and compared with species from the West Pacific. Phos elegantissimus Hayashi & Habe, 1965, P. hirasei Sowerby, 1913 and P. laevis Kuroda & Habe in Habe, 1961 are recorded from Mozambique and/or from Madagascar, hereby extending their known range considerably into the western Indian Ocean. The East African specimens formerly assigned to Phos roseatus Hinds, 1844 are found to differ from this West Pacific species. In total, five species are described as new: Phos ganii sp. nov., P. geminus sp. nov., P. ladoboides sp. nov., P. pulchritudus sp. nov. and P. testaceus sp. nov.